Nutritional Recovery with a Soybean Diet after Weaning Reduces Lipogenesis but Induces Inflammation in the Liver in Adult Rats Exposed to Protein Restriction during Intrauterine Life and Lactation. (29th March 2015) - Reis, Sílvia Regina de Lima; Feres, Naoel Hassan; Ignacio-Souza, Leticia Martins; Veloso, Roberto Vilela; Arantes, Vanessa Cristina; Kawashita, Nair Honda; Colodel, Edson Moleta; Botosso, Bárbara Laet; Reis, Marise Auxiliadora de Barros; Latorraca, Márcia Queiroz
Abstract : We evaluated the effects of postweaning nutritional recovery with a soybean flour diet on de novo hepatic lipogenesis and inflammation in adult rats exposed to protein restriction during intrauterine life and lactation. Rats from mothers fed with protein (casein) in a percentage of 17% (control, C) or 6% (low, L) during pregnancy and lactation were fed with diet that contained 17% casein (CC and LC groups, resp.) or soybean (CS and LS groups, resp.) after weaning until 90 days of age. LS and CS rats had low body weight, normal basal serum triglyceride levels, increased ALT concentrations, and high HOMA-IR indices compared with LC and CC rats. The soybean diet reduced PPAR γ as well as malic enzyme and citrate lyase contents and activities. The lipogenesis rate and liver fat content were lower in LS and CS rats relative to LC and CC rats. TNF α mRNA and protein levels were higher in LS and CS rats than in LC and CC rats. NF- κ B mRNA levels were lower in the LC and LS groups compared with the CC and LC groups. Thus, the soybean diet prevented hepatic steatosis at least in part through reduced lipogenesis but resulted in TNF α -mediated inflammation.